2011
DOI: 10.1007/s11547-011-0740-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-ARDS pulmonary fibrosis in patients with H1N1 pneumonia: role of follow-up CT

Abstract: In patients with H1N1 pneumonia, post-ARDS pulmonary fibrosis is not a rare complication. Therefore, a CT scan should be performed in all patients with severe clinical findings. Our study demonstrated that in these patients, fibrosis could present a different spatial distribution and a different temporal trend, with delayed late onset; moreover, in one case, the signs of interstitial lung disease partially regressed over time. Therefore, CT should be considered not only in the diagnostic stage, but also during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 27 publications
(38 reference statements)
6
59
1
1
Order By: Relevance
“…The signs of fibrosis (including parenchymal bands, irregular linear opacities, interfaces and traction bronchiectasis) in most of our patients were gradually regressed with time [1]. Other researchers also reported that pulmonary fibrosis in patients with H1N1 pneumonia was not a rare complication and could partially regress over time [2,3]. A few of our patients with influenza A (H1N1) virus infection responded quickly to the corticosteroids.…”
supporting
confidence: 57%
“…The signs of fibrosis (including parenchymal bands, irregular linear opacities, interfaces and traction bronchiectasis) in most of our patients were gradually regressed with time [1]. Other researchers also reported that pulmonary fibrosis in patients with H1N1 pneumonia was not a rare complication and could partially regress over time [2,3]. A few of our patients with influenza A (H1N1) virus infection responded quickly to the corticosteroids.…”
supporting
confidence: 57%
“…This finding is not completely specific because the reversibility of bronchial dilatation has also been described in the late stages of ARDS [60,61].…”
Section: Acute Respiratory Distress Syndrome | M Zompatori Et Almentioning
confidence: 89%
“…These results would need to be interpreted in light of the patient’s history and clinical course. For example, mechanical ventilation parameters [16, 17] and specific risk factors underlying ARDS development [69] have been associated with a more protracted clinical course and subsequent fibrotic lung disease.…”
Section: Identification Of Excessive Fibroproliferation May Help Guidmentioning
confidence: 99%
“…A separate group has confirmed the utility of HRCT obtained during the acute phase of pathologically confirmed diffuse alveolar damage, and found that increased radiological lung involvement, as well as traction bronchiectasis, were associated with death [80]. Finally, published studies of the 2009 H1N1 epidemic indicate that HRCT is similarly useful in predicting mortality and long-term morbidity in patients with ARDS from influenza A [69, 81]. Our group’s recent observations complement and add to these investigations and suggest that HRCT performed early in the course of ARDS may prognosticate functional impairment in survivors months after discharge [18].…”
Section: Identification Of Excessive Fibroproliferation May Help Guidmentioning
confidence: 99%